Frequency of comorbidities in patients with osteoarthritis and their impact on pain and physical function - Islam, Mohammed Taherul; Sultan, Mohammad Imtiaz; Deb, Aparna; Dey, Protyay; Arif, M. Saiful; Barua, Anupam; Hassan, Muhammad Habib; Romana, Shamshed Nesreen; Mamun, Tousif Bin; Simanto (International Journal of Research in Medical Sciences, 2026)
Background: Osteoarthritis (OA) is one of the commonest morbidities in older age population and the most common reason for restricted activity in their daily life. The prevalence of other disabling condition also rises with age and some common chronic condition can be found along with OA. The aim of this study was to identify frequency of comorbidities in patients with OA and impact of comorbidities on pain and physical function of the patients. Methods: Self-reported comorbidities, clinical examinations and relevant investigations findings were recorded in a case record form. Depression and anxiety were measured by PHQ-9 and GAD-7 scale respectively. Pain of joint and physical function was measured by WOMAC questionnaire. Results: The mean of the age, BMI (body mass index) and duration of pain was respectively 56.83 (±8.28) years, 26.01 (±4.1) kg/m2 and 4.1 (±2.9) years. Male female ratio was 1:2.23. About one fifth of the patients (19.1%) reported no associated comorbid conditions and approximately three fourth of patients (70%) reported one or two comorbid conditions and another 11% reported three or more comorbid conditions. Of the comorbid conditions the most frequent was HTN (45.5%), followed by DM (20.9%), depression (20.9%) and anxiety (13.6%). The mean pain and physical function scores were 17.8±7.1 and 63.6±21.7 respectively. Conclusions: In summary, the OA patients showed a high frequency of comorbid conditions including depression, which can impact the pain and physical function of those patients. Such results show the need for investigating and treating those comorbidities in OA patients.